1996
DOI: 10.1021/om960203p
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Assisted Formation of Carbon−Carbon Bonds. 6.1 Study of the Reactivity of (o-Formylaryl)- or (o-Acetylaryl)palladium Complexes with Alkynes. Synthesis of Indenones and Indenols

Abstract: The reaction of (PhCH2PPh3)2[Pd(R1)Cl(μ-Cl)]2 (1; R1 = 6-formyl-2,3,4-trimethoxyphenyl) with PhC⋮CPh gives a 6.5:1 mixture of 4,5,6-trimethoxy-2,3-diphenylindenone (2)and 4,5,6-trimethoxy-2,3-diphenyl-1H-indenol (3). When the same reaction is carried out with MeO2CC⋮CCO2Me or with Me3SiC⋮CSiMe3, the compounds 4,5,6-trimethoxy-2,3-bis(methoxycarbonyl)indenone (4) and R1C⋮CSiMe3 (5) are obtained, respectively. The reactions of PhC⋮CPh with [Pd(R1)Cl(bpy)] (6; bpy = 2,2‘-bipyridine), in the presence of AgClO4, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 52 publications
4
85
1
Order By: Relevance
“…The angles between adjacent atoms in the coordination sphere of palladium are close to the expected value of 90°with the most noticeable distortions corresponding to the N(2)-Pd(1)-N(3) angle of 78.85 (8) is longer than Pd(1)-N(2) distance, showing the stronger trans influence of the C(1) carbon atom as compared to the Cl(1) chlorine. The Pd(1)-C(1) bond distance of 1.980(3) Å is somewhat shorter than the value predicted from their covalent radii [31] but similar to values found earlier [21,23,[28][29][30].…”
Section: Crystal Structure Of 3asupporting
confidence: 84%
“…The angles between adjacent atoms in the coordination sphere of palladium are close to the expected value of 90°with the most noticeable distortions corresponding to the N(2)-Pd(1)-N(3) angle of 78.85 (8) is longer than Pd(1)-N(2) distance, showing the stronger trans influence of the C(1) carbon atom as compared to the Cl(1) chlorine. The Pd(1)-C(1) bond distance of 1.980(3) Å is somewhat shorter than the value predicted from their covalent radii [31] but similar to values found earlier [21,23,[28][29][30].…”
Section: Crystal Structure Of 3asupporting
confidence: 84%
“…22 We have reported the synthesis of ortho-palladated complexes by transmetalation reactions, using arylmercurials, by oxidative additions of the corresponding haloarenes to palladium(0) species, or through orthopalladation processes. The first method has allowed us to prepare aryl-palladium complexes bearing CHO, [23][24][25] etamidic acids, 39 and with CO to give aroyl-palladium complexes, [28][29][30][31]37, 39 3-methylenephthalides and 3-ethoxy-3-methyl-3H-isobenzofuran-1-one 39 or, in the presence of O 2 , palladium benzoate complexes. 28,29 We have reported that certain 2,3,4-trimethoxy-6-formylphenylpalladium complexes undergo a rare rearrangement, involving a positional change between the formyl group and the palladium moiety with breaking and reforming of C-C and C-Pd bonds, to give the corresponding 3,4,5-trimethoxy-2-formylphenylpalladium isomers (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…32,47,56,57]. The Pd-N(3) bond length shows the greater trans influence of the C(1) carbon as compared to the P(1) phosphorus.The coordination sphere around palladium [Pd(1), C(1), N(2), N(3), P(1)] is planar (r.m.s.…”
mentioning
confidence: 99%